Nilai Moral dalam Novel Guru Aini Karya Andrea Hirata - Ayu Pramusuari; Sri Rahayu (UIR Press, 2023)
The study in this research focuses on moral values ​​seen from the aspects of responsibility, conscience, and obligation. This research uses a qualitative approach with descriptive methods. The data taken from this study are words, sentences, and paragraphs that contain moral values ​​related to responsibility, conscience, and obligation. The data source in this study is the entire contents of the novel Guru Aini which was published in 2019, written by Andrea Hirata. The results of data analysis in this study concluded that the moral values ​​from the aspect of responsibility contained in Andrea Hirata's Novel Guru Aini contained 6 data. such as: The character Desi, who is ready to take risks wherever she is placed to teach, becomes a math teacher. Aini's character, she has promised not to humiliate herself by being dishonest with a desi teacher. The moral value of the conscience aspect is contained in the Novel Guru Aini by Andrea Hirata. There are 4 data. such as: Desi figure, a desi who is ready to work anywhere because she feels that Indonesia lacks math teachers. The moral value from the obligatory aspect is found in the Novel Guru Aini by Andrea Hirata. There are 8 data. such as: The figure of Desi, desi thanked the crew members who had helped her carry the goods to get off the ship. Figures of high school students, before entering the classroom, they shook hands and kissed the hand of their teacher, a desi teacher who was already standing in front of the class.